(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Research productivity is an essential criteria for the recognition, promotion and career advancement of librarians. However, previous studies have established low level of research productivity of librarians in South-South, Nigeria making it a subject of concern to the university and library management. While existing studies have analyzed bibliometric data of librarians' publications, some studies have shown that research mentoring can have an effect on research productivity. However, the variable has not been fully measured in the literature to determine its influence on research productivity. Therefore, this study investigated the influence research mentoring ( problem identification, literature search, collaboration, research design and time management) on research productivity of academic librarians in universities in South-South, Nigeria. The study adopted survey research design. The population comprised 229 academic librarians in 30 universities in South-South, Nigeria. Total enumeration sampling technique was used for the study. A structured and validated questionnaire was used for data collection. Cronbach’s alpha reliability coefficients for the constructs ranged from 0.82 to 0.88. The response rate was 86.4%. Data were analyzed using descriptive and inferential (simple and multiple regression) statistics at 5% level of significance. Findings revealed that research mentoring (Adj.R2= 0.68, F(1, 198) = 439.50, p < 0.05) had a significant influence on research productivity. The study concluded that research mentoring had a significant influence on research productivity of academic librarians in universities in South-South, Nigeria. Therefore, it was recommended that the management of universities, should also institutionalize research mentoring programs to enhance research productivity.